Flow Studies using Laser Anemometry Technique in a Small Power Unit Radial Inflow Turbine - Sohail H. Zaidi; Robin L. Elder (International Journal of Rotating Machinery)
T-100 is a multipurpose small power unit developed by Sundstrand Power Systems (USA). An extensive research programme was launched for the detailed tests of the rig components including inlet protection system, Compressor stage, Combustor and the Turbine stage. Turbomachinery Group at Cranfield was involved in the study of the Turbine unit used in this programme. From the design point of view, detailed aerodynamics in these small units are of great interest especially where high velocities and narrow passages are involved. Experimental study was carried out to investigate the flow in the region between the nozzle guide vanes and the turbine rotor entry. The main concern was to find out how the nozzle guide vane flow was modified by the rotor and how the rotor flow was affected by the nozzle guide vanes. Laser measurements were taken at these positions for various flow conditions. An other area which needs considerable attention is downstream of the turbine rotor where the turning of flow and mixing process make the situation very complicated. Laser studies were undertaken in that region and to gain more confidence on laser results, a Cobra pressure probe was traversed at these stations. This paper describes various steps undertaken to obtain laser results within the machine. At the end typical laser results have been presented and discussed.